Genome Sequencing and Comparative Genomic Analysis of Attenuated Strain Gibellulopsis nigrescens GnVn.1 Causing Mild Wilt in Sunflower - Baozhu Dong; Wanyou Liu; Yingjie Zhao; Wei Quan; Lijun Hao; Dong Wang; Hongyou Zhou; Mingmin Zhao; Jianxiu Hao (Journal of Fungi)
Gibellulopsis nigrescens, previously classified in the Verticillium genus until 2007, is an attenuated pathogen known to provide cross-protection against Verticillium wilt in various crops. To investigate the potential mechanisms underlying its reduced virulence, we conducted genome sequencing, annotation, and a comparative genome analysis of G. nigrescens GnVn.1 (GnVn.1), an attenuated strain isolated from sunflower. The genome sequencing and annotation results revealed that the GnVn.1 genome consists of 22 contigs, with a total size of 31.79 Mb. We predicted 10,876 genes, resulting in a gene density of 342 genes per Mb. The pathogenicity gene prediction results indicated 1733 high-confidence pathogenicity factors (HCPFs), 895 carbohydrate-active enzymes (CAZys), and 359 effectors. Moreover, we predicted 40 secondary metabolite clusters (SMCs). The comparative genome analysis indicated that GnVn.1 contains more CAZys, SMCs, predicted effectors, and HCPF genes than Verticillium dahliae (VdLs.17) and Verticillium alfalfae (VaMas.102). The core–pan analysis results showed that GnVn.1 had more specific HCPFs, effectors, CAZys, and secreted protein (SP) genes, and lost many critical pathogenic genes compared to VdLs.17 and VaMs.102. Our results indicate that the GnVn.1 genome harbors more pathogenicity-related genes than the VdLs.17 and VaMs.102 genomes. These abundant genes may play critical roles in regulating virulence. The loss of critical pathogenic genes causes weak virulence and confers biocontrol strategies to GnVn.1.